Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/mgg3.308
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin-converting enzyme insertion/deletion polymorphism rs4340 associates with habitual physical activity among European American adults

Abstract: BackgroundThe angiotensin‐converting enzyme (ACE) insertion/deletion (I/D) polymorphism (rs4340) (ACE DIP) accounts for half of the variability in plasma ACE concentrations. ACE has been widely studied for its influence on sports performance; however, research on its influence in physical activity is limited and inconsistent. We examined the influence of the ACE DIP on physical activity among 461 European Americans.MethodsSubjects completed the Paffenbarger Physical Activity Questionnaire for weekly walking di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…In line with previous reviews [ 12 , 19 , 20 ] we noted that phenotype definitions of physical activity varied considerable between studies, including constructs such as walking distance [ 32 ], low-intensity physical activity [ 45 , 52 ], moderate intensity physical activity [ 34 , 36 , 49 ], vigorous physical activity [ 34 , 37 ], energy expenditure [ 29 , 31 , 48 ], engagement in sports activities [ 44 , 51 ], meeting recommended levels of physical activity [ 50 ], and physical activity level from childhood to adolescence [ 46 ]. Moreover, these phenotype definitions were in many studies based on instruments with poor validity.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In line with previous reviews [ 12 , 19 , 20 ] we noted that phenotype definitions of physical activity varied considerable between studies, including constructs such as walking distance [ 32 ], low-intensity physical activity [ 45 , 52 ], moderate intensity physical activity [ 34 , 36 , 49 ], vigorous physical activity [ 34 , 37 ], energy expenditure [ 29 , 31 , 48 ], engagement in sports activities [ 44 , 51 ], meeting recommended levels of physical activity [ 50 ], and physical activity level from childhood to adolescence [ 46 ]. Moreover, these phenotype definitions were in many studies based on instruments with poor validity.…”
Section: Discussionsupporting
confidence: 85%
“…In line with previous reviews [12,19,20] we noted that phenotype definitions of physical activity varied considerable between studies, including constructs such as walking distance [32], low-intensity physical activity [45,52], moderate intensity physical activity [34,36,49], vigorous physical activity [34,37], energy expenditure [29,31,48], engagement in sports activities [44,51], meeting Table 3 Genotype-phenotype associations in medium (6-8.5 points) and high (≥9 points) quality candidate gene studies and GWAS. For GWAS, results with a genome-wide significance level of p < 5 × 10 −8 or lower are presented.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In a group of 1130 Mexican youths, those who had at least one copy of the minor allele for SNPs in ACE (rs8066276, p=0.012) were more likely to meet PA recommendations 61 . A study in European American adults also showed that the ACE I/D polymorphism rs4340 associates with weekly walking distance 62 . Other candidate genes have been studied such as the ankytin repeat domain 6 gene (ANKRD6) 63 (MC4R) which is located on chromosome 18 which was identified by a previous linkage study 29 .…”
Section: Candidate Genes For Physical Activitymentioning
confidence: 97%